Why the theory of comparative advantage is wrong. (1st January 2011) - Fletcher, Ian
The theory of comparative advantage is widely misunderstood to demonstrate the universal superiority of free trade. In fact, the theory depends upon a number of key assumptions and fails if they are relaxed. Empirically, many of these assumptions are highly questionable, if not demonstrably false. Among them are an absence of externalities, a lack of international capital mobility, and no income-inequality effects. Also included are assumptions about optimal short- and long-term growth strategies being identical and domestic factor mobility being costless.